Islamic Legal Hermeneutics on Riba in Digital Banking: Contextualizing Imam al-Qurṭubī’s Exegesis of Qur’an 2:275 - Muharir Muharir; Irfan Kuncoro; Agus Yosep Abduloh; Ulummudin Ulummudin; Hisam Ahyani (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
This study explores the application of riba (interest-based transactions) within the context of digital banking, with a specific focus on the BRImo application developed by Bank Rakyat Indonesia (BRI). Using a hermeneutic approach, it examines Imam Al-Qurthubi’s classical tafsir on Surah Al-Baqarah verse 275 to contextualize Islamic legal principles in contemporary financial practices. The research adopts a qualitative-descriptive method to analyze textual interpretations of riba while also identifying the ethical, social, and economic implications of these interpretations in digital financial systems. Findings indicate that Imam Al-Qurthubi strongly opposes riba as a form of financial exploitation, a stance that remains relevant in evaluating modern digital banking operations. Moreover, the study discusses how BRImo’s integrated social finance features—such as zakat and infaq services—represent an effort to align digital banking with Islamic ethical values. While this article provides a theoretical framework through classical tafsir, it also underscores the need for further empirical investigation and comparative analysis with other scholarly interpretations to enhance the practical applicability of non-riba models in digital finance. This research contributes to the discourse on contextualized Islamic law by bridging classical legal thought with emerging financial technologies, offering insight into how Islamic jurisprudence can inform the development of ethical, Shari’ah-compliant digital banking system